Performance of the Fracture Risk Assessment Tool Associated with Muscle Mass Measurements and Handgrip to Screen for the Risk of Osteoporosis in Young Postmenopausal Women - Sonnenfeld,Marina Martinelli (2022)
Abstract Objective To evaluate the improvement in screening accuracy of the Fracture Risk Assessment Tool (FRAX) for the risk of developing osteoporosis among young postmenopausal women by associating with it clinical muscle mass measures. Methods A sample of postmenopausal women was submitted to calcaneal quantitative ultrasound (QUS), application of the FRAX questionnaire, and screening for the risk of developing sarcopenia at a health fair held in the city of São Bernardo do Campo in 2019. The sample also underwent anthropometric measurements, muscle mass, walking speed and handgrip tests. A major osteoporotic fracture (MOF) risk ≥ 8.5% on the FRAX, a classification of medium risk on the clinical guideline of the National Osteoporosis Guideline Group (NOGG), and a QUS T-score ≤ -1.8 sd were considered risks of having low bone mass, and QUS T-score ≤ -2.5sd, risk of having fractures. Results In total, 198 women were evaluated, with a median age of 64±7.7 years, median body mass index (BMI) of 27.3±5.3 kg/m2 and median QUS T-score of -1.3±1.3 sd. The accuracy of the FRAX with a MOF risk ≥ 8.5% to identify women with T-scores ≤ -1.8 sd was poor, with an area under the curve (AUC) of 0.604 (95% confidence interval [95%CI]: 0.509-0.694) for women under 65 years of age, and of 0.642 (95%CI: 0.571-0.709) when age was not considered. Including data on muscle mass in the statistical analysis led to a significant improvement for the group of women under 65 years of age, with an AUC of 0,705 (95%CI: 0.612-0.786). The ability of the high-risk NOGG tool to identify T-scores ≤ -1.8 sd was limited. Conclusion Clinical muscle mass measurements increased the accuracy of the FRAX to screen for osteoporosis in women aged under 65 years.